Dexmedetomidine for Postoperative Sedation Following Stereotactic Lead Placement - Xu, Hope; Bui, Anthony H.; La Vega-Talbott, Maite; Zackai, Sheemon P. (Journal of Pediatric Neurology, 2020)
Dexmedetomidine has become an increasingly popular alternative to benzodiazepines and opioids as a safe agent for sedation and pain control, especially in pediatric populations. In this study, we present a case of postoperative use of dexmedetomidine in a pediatric patient, with a known history of behavioral difficulties, who underwent stereotactic lead placement for medically refractory epilepsy.
Keywords: dexmedetomidine; Precedex; stereoelectroencephalography; stereotactic lead placement; epilepsy; sedation